Evaluation of two different desensitizing agents in the treatment of dentin hypersensitivity: Case Report - Mateus Lotti Amaral; Daniel Galafassi; Juliane Pereira Butze (Faculdade Meridional IMED, 2019)
Aim: The following work reported in a clinical case the efficacy of Nano-P® desensitizer and acidulated fluoride in a patient with dentin hypersensitivity. Methods: the patient's mouth was divided for the application of each treatment. In the quadrants 1 and 3 the Nano P® desensitizer was used and in the 2 and 4 quarters the acidulated fluoride was used, with weekly applications for 4 weeks. Density hypersensitivity was evaluated by the Visual Analogue Scale (VAS) through osmotic and tactile stimulation. Results: For both treatments, it was observed a decrease in the degree of Hypersensitivity reported by the patient during the consultations, with different action times for each desensitizing agent, due to its differentiated characteristics and mechanisms of action, as well as differences in relation to the comfort reported in the two techniques by the patient participating in the study. Conclusions: The desensitizing agents evaluated in this study were effective in reducing dentin sensitivity after 5 evaluation visits.